2018
DOI: 10.15345/iojes.2018.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Examining Elementary Pre-service Teachers’ Science, Technology, Engineering, and Mathematics (STEM) Teaching Intention

Abstract: This study aims at examining elementary pre-service teachers' integrative STEM intentions. In this quantitative study, data were gathered from 401 elementary pre-service teachers who were enrolled in two public universities. Results of the study revealed that pre-service teachers' integrative STEM intentions were positive in general. In addition, regarding knowledge, attitude, value, subjective norm, perceived behavioral control, and behavioral intention, elementary pre-service teachers seemed to hold positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 7 publications
(20 reference statements)
2
16
0
3
Order By: Relevance
“…Additionally, it was concluded that the STEM attitudes and achievements of female students were higher than those of male students (Karakaya & Avgın, 2016;Knezek, Christensen & Tylor-Wood, 2011). There are also results showing that there is no significant difference between teachers or pre-service teachers' STEM awareness and STEM attitudes based on the gender variable (Aydın, Saka, & Guzey, 2017;Bakırcı & Karışan, 2018;Çevik, 2017;Hacıömeroğlu, 2017;Simon, Wagner, & Killion, 2017). These results supported the results of this study.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, it was concluded that the STEM attitudes and achievements of female students were higher than those of male students (Karakaya & Avgın, 2016;Knezek, Christensen & Tylor-Wood, 2011). There are also results showing that there is no significant difference between teachers or pre-service teachers' STEM awareness and STEM attitudes based on the gender variable (Aydın, Saka, & Guzey, 2017;Bakırcı & Karışan, 2018;Çevik, 2017;Hacıömeroğlu, 2017;Simon, Wagner, & Killion, 2017). These results supported the results of this study.…”
Section: Discussionsupporting
confidence: 86%
“…A related study carried out by Aydın, Saka and Guzey (2017) revealed that secondary school students' levels of attitudes towards STEM did not differ across gender, school type and parents' educational background. Similarly, in another study, Hacıömeroğlu (2017) reported that the elementary school preservice teachers' mean scores regarding the sub-dimensions of the STEM teaching tendency scale (value, attitude, knowledge (and so on) did not differ significantly with respect to the variable of gender. Karakaya and Avgın (2016), in their study, found that parents' educational background did not have much influence on their secondary school children's attitudes towards STEM and that the variables of gender and grade level did not have any influence on the secondary school students' attitudes towards STEM.…”
Section: Discussionmentioning
confidence: 78%
“…Yenilmez and Balbağ (2016) have found that the attitudes of preservice science and mathematics teachers towards STEM are generally positive and preservice science teachers' attitudes towards STEM are generally more positive than those of preservice mathematics teachers. Hacıömeroğlu (2017) indicated that the STEM teaching intention levels of the preservice primary school teachers were generally positive. In addition, it was determined that the opinions of the preservice teachers were positive in the knowledge, attitude, value, subjective and behaviour subscales.…”
Section: Discussionmentioning
confidence: 97%
“…Primary school teachers are responsible for teaching science and mathematics to 1-4 graders. However, it has been noted that preservice primary school teachers do not have sufficient knowledge about STEM education Hacıömeroğlu, 2017).…”
Section: Tartışma Ve Sonuçmentioning
confidence: 99%
See 1 more Smart Citation